A Unidade Multidisciplinar de Memória e Arquivo Histórico da UFSCar (UMMA): diretrizes para uma política de recuperação, preservação e salvaguarda da memória institucional - Ramalho, Claudia de Moraes Barros (Universidade Federal de São Carlos, 2022)
The theme of memory, as an object of research or action in the different disciplinary areas, is challenging as it requires not only curiosity and the search for knowledge, but professional qualification and, above all, determination and passion. For this research, UFSCar is the locus where the implementation of the Multidisciplinary Unit of Memory and Historical Archive (UMMA) is located and this is the inspiring motto to reflect on the diversity of institutional historical sources, their intertwining, entanglement and complementarities, instigating thought to understand all of this, which is reflected in a policy of preserving and safeguarding institutional memory. The main objective of this research is to present a proposal for organizing the University's memory collections by levels of description and grouping into thematic categories and thereby promoting the rescue, preservation and safeguarding of institutional memory. Thus, the result of this study would compose the memory policy at UFSCar. In order to reach the objectives, this research is characterized as being exploratory, descriptive and explanatory of a qualitative nature. The creation of a memory space within the scope of the Institutional Repository is an important initiative for safeguarding UFSCar's memory collections. In addition to the empirical data collected, which allowed a survey of the collections of documents related to the history of UFSCar, this research was also based on a bibliographic and documental survey for the elaboration of analyzes aimed at gathering elements for a proposal for a memory policy through the categorization and typology of information sources that make up the University's historical collections based on thematic categories that could encompass the entire institutional memory. Implementing a memory policy at UFSCar is essential to preserve the institution's memory, safeguard it and, above all, strengthen its identity. The rescue of institutional memory by the servers is equally important for the community and as a way of appreciating all the years of dedication of those who contributed to the construction of the Federal University of São Carlos.
The Multidisciplinary Unit of Memory and Historical Archive of UFSCar (UMMA): guidelines for a policy of recovery, preservation and safeguarding of institutional memory
Keywords: Memória institucional; Preservação; Salvaguarda da memória; Patrimônio; Políticas de memória; Institutional memory; Safeguard memory; Patrimony; Memory policies; CIENCIAS HUMANAS